Hybrid method of strain estimation in optical coherence elastography using combined sub‐wavelength phase measurements and supra‐pixel displacement tracking. Issue 5 (13th November 2015) - Zaitsev, Vladimir Y.; Matveyev, Alexander L.; Matveev, Lev A.; Gelikonov, Grigory V.; Gubarkova, Ekaterina V.; Gladkova, Natalia D.; Vitkin, Alex
Abstract : A novel hybrid method which combines sub‐wavelength‐scale phase measurements and pixel‐scale displacement tracking for robust strain mapping in compressional optical coherence elastography is proposed. Unlike majority of OCE methods it does not rely on initial reconstruction of displacements and does not suffer from the phase‐wrapping problem for super‐wavelength displacements. Its robustness is enabled by direct fitting of local phase gradients obviating the necessity of phase unwrapping and error‐prone numerical differentiation. Furthermore, axial displacements significantly exceeding not only the optical wavelength, but pixel scales (i.e., multiple wavelengths) can be efficiently tracked and compensated. This feature strongly reduces errors in phase‐gradient estimation and ensures high robustness with respect to both additive and decorrelation noises.Illustration of exceptionally high tolerance of the proposed method to noises: contrast of only 25% in the stiffness of the layers is clearly seen in the strain map even for equal intensities of the OCT signal and additive noise (SNR = 0 dB). Abstract : A novel hybrid method which combines sub‐wavelength‐scale phase measurements and pixel‐scale displacement tracking for robust strain mapping in compressional optical coherence elastography is proposed. Its robustness is enabled by direct fitting of local phase gradients obviating the necessity of phase unwrapping and error‐prone numerical differentiation. The significantly extended range of measurable strains strongly reduces errors in phase‐gradient estimation and ensures high robustness with respect to both additive and decorrelation noises.Illustration of exceptionally high tolerance of the proposed method to noises: contrast of only 25% in the stiffness of the layers is clearly seen in the strain map even for equal intensities of the OCT signal and additive noise (SNR = 0 dB).